Pengaruh Paket Bimbingan Konseling Covid-19 Berbasis Ajaran Islam dan Dakwah dalam Mencegah Penyebaran Covid di Kota Makassar - Hadis, Abdul; B, Nurhayati; Usman, Usman (Seminar Nasional LP2M UNM, 2023)
Abstract. The fact shown that distributed Covid-19 infection to the peoples of Makassar City not yet final. This caused application, understanding, and knowledge of peoples is low about cleaning and dangerous of Covid-19. Therefore, the goal of this research is for product of counseling and guidance Covid-19 based dakwah dan Islam. From this development research, opportunited fist year birth product Covid-19 Counseling and Guidance dan at second year of this research is experimentation this product fot konow effect to preventive distribution infection of Covid-19 at Makassar City. This research design is development research with adoption of Dick and Carey model pasca adaptation by researchers team. Keywords: Counseling and guidance, Covid-19, Islam and Dakwah